Synergistic Effect of Licorice (Glycyrrhiza glabra) Root Powder, Asparagus (Asparagus racemosus) Root Powder and Lemongrass (Cymbopogon citratus) Oil on the Growth Performance of Commercial Broiler Chicken - Pappula, Radhika (Indian Journal of Animal Nutrition, 2023)
The present study was conducted to evaluate the synergistic effect of licorice root powder (LRP), asparagus root powder (ARP) and lemongrass oil (LGO) on the performance of broiler chickens. A total of 300-day-old commercial male broiler chicks (Vencobb 400) were randomly distributed into six treatments having ten replicates with five birds in each replicate and were raised for a period of 42 days. Diets contain T1 as control i.e., basal diet (BD) without any growth promoter, T2 – 0.05% antibiotic (AB), T3 – 1% LRP + 2% ARP, T4 -1% LRP + 250mg LGO, T5 – 2% ARP + 250mg LGO and T6 – 1% LRP + 2% ARP + 250mg LGO. Results revealed that significantly (P<0.05) increased body weight gain and better feed conversion ratio was noticed in LRP + LGO combination group followed by other combinations and antibiotic when compared to control at 42 d of age. No significant effect was noticed in feed consumption by different treatments. Therefore, it can be concluded that supplementation of licorice root powder (1%), asparagus root powder (2%) and lemongrass oil (250mg) combination were found to be beneficial in broiler chicken for its remarkable results in terms of growth performance and can be a better alternative to antibiotic growth promoter.